Embodied cognition perspectives within early executive function development - Pearce, Z. Reagan; Miller, Stephanie E. (Frontiers in Cognition, 2025)
The development of executive function (EF) has become a central focus in early cognitive development research. While movement is frequently used to measure EF in young children and may significantly contribute to its development, many leading EF theories do not fully explore the role of movement. This review investigates the critical role of movement in the development of EF during early childhood through the framework of embodied cognition, particularly drawing on the central themes outlined by Lawrence Shapiro. By applying Shapiro's themes, this narrative review examines whether and how these embodied cognition concepts are integrated into leading theories of EF development. The analysis identifies key gaps where current theories could benefit from a deeper incorporation of embodied cognition. This work aims to support future research that emphasizes the importance of movement in fostering EF during early childhood.